+0  
 
0
63
1
avatar

8[7 - (6x - 6)] + 6x = 0.

Guest Aug 7, 2017
Sort: 

1+0 Answers

 #1
avatar+76222 
+1

8[7 - (6x - 6)] + 6x = 0      simplify inside the brackets first

 

8 [ 7 - 6x + 6 ]  + 6x  =  0

 

8 [ 13 - 6x ] + 6x  = 0

 

104 - 48x + 6x  = 0

 

104 - 42x  = 0    add 42x to both sides

 

104  =  42x   divide both sides by 42

 

104 / 42  = x  =  52 / 21

 

 

cool cool cool

CPhill  Aug 7, 2017

18 Online Users

avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details